Korelasi Pemahaman Keislaman Istri dengan Pembentukan Keharmonisan Rumah Tangga - Susiana Susiana; Ahmad Rozai Akbar; Maruli Siregar (Hikmah, 2023)
Islam is a source of guidance for human life, including in households. Couples who practice these teachings, should be happy, and vice versa. But the problem is that people's levels of understanding are different about Islamic teachings, which of course affects their life journey, including the household. Therefore this study aims to determine the influence of the wife's Islamic understanding on the formation of household harmony. This research was conducted in the Griya Pulai Sakinah Dumai housing complex. Where the wives who are Muslim in the housing are the research population, with a sample determination of fifty people. The research method used is correlation-based quantitative. The results of the study show that a small proportion of family members are very knowledgeable about religious understanding in general, and this understanding is correlated with household harmony. There are several influencing factors, namely ideal communication, understanding of sakinah, mawaddah, and warahmah, understanding of rights and obligations in Islam, applying religious knowledge in acting and making decisions, accepting partner deficiencies, respecting and being open to each other. The results of this study can be a reference for preachers, in conducting pre-marital and post-wedding coaching.Keywords: Inheritance system, Malay adat, Islamic law, Shulh.